2009
DOI: 10.1007/s12041-009-0062-6
|View full text |Cite
|
Sign up to set email alerts
|

Channelrhodopsins provide a breakthrough insight into strategies for curing blindness

Abstract: Photoreceptor cells are the only retinal neurons that can absorb photons. Their degeneration due to some diseases or injuries leads to blindness. Retinal prostheses electrically stimulating surviving retinal cells and evoking a pseudo light sensation have been investigated over the past decade for restoring vision. Currently, a gene therapy approach is under development. Channelrhodopsin-2 derived from the green alga Chlamydomonas reinhardtii, is a microbial-type rhodopsin. Its specific characteristic is that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 75 publications
1
17
0
Order By: Relevance
“…ERGs and VEPs were recorded as described previously12151638. Briefly, rats were dark-adapted overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ERGs and VEPs were recorded as described previously12151638. Briefly, rats were dark-adapted overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Safety studies were also performed in rats and marmosets11, which showed that no immunological responses12 were induced by the continuous expression of a ChR2 gene that was derived from the unicellular green algae Chlamydomonas reinhardtii 1314, rather than from a human source. Gene therapy using ChR2 thus represents a potential method for restoring vision in blind patients15. However, ChR2-expressing rats exhibiting photoreceptor degeneration could only detect wavelengths less than 540 nm because of the limitation of the ChR2 action spectrum16.…”
mentioning
confidence: 99%
“…24.6 ). The shortening of the P1 latency is derived from a short-cut in the transmission of inner retinal cells (Tomita et al 2009b ). These results indicate that ChR2 is a useful tool for restoring vision.…”
Section: Analysis By Retinal Electrical Physiologymentioning
confidence: 99%
“…Readers interested in more specific details of the field are referred to the published reviews on the subject of optogenetics and visual restoration. [1][2][3][4][5][6][7][8][9] An issue of Nature in 2010 focused on optogenetics as ''Method of the Year'' also contains an excellent explanatory video of the technique in the f o l l o w i n g l i n k : h t t p : / / w w w . y o u t u b e .…”
Section: Overviewmentioning
confidence: 99%